Pemanasan Ohmik Roti Bebas Gluten Berbasis Tepung Kedelai Hitam-Beras: Kajian Suhu Dan Daya - Jenri Parlinggoman Hutasoit; Aji Sutrisno; Aniswatul Khamidah (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2023)
Ohmic heating is a heating process that works based on passing electric current through resistive materials. This heating is known to have advantages such as producing uniform heat and a high heating rate. The purpose of this study was to determine the changes in temperature and power used in ohmic heating of gluten-free bread based on black soybean flour substituted with rice flour. The bread batter formulation in this research was based on black soybean flour with rice flour substitution (50, 40, 30, 20, 10 and 0%). The parameters of temperature and electrical power were obtained from the data logger. The data is calculated in formulas and displayed in curves as a function of time during the process. The results showed that the addition of rice flour or the higher the ratio of rice flour in the dough showed a rapid rate of temperature increase at its maximum value, as well as the initial electrical power value used during heating. Based on the calculation of the time needed to reach the optimal temperature of about 97 oC in each treatment, it was found that the treatment of 50% black soy flour + 50% rice flour (8 minutes 10 seconds), the treatment of 60% black soy flour + 40% rice flour (8 minutes 30 seconds), the treatment of 70% black soy flour + 30% rice flour (8 minutes 60 seconds), the treatment of 80% black soy flour + 20% rice flour (9 minutes 40 seconds), the treatment of 90% black soy flour + 10% rice flour (11 minutes 30 seconds), and the treatment of 100% black soy flour + 0% rice flour (12 minutes).